Magnetic actuators and sensors - Brauer, John R., 1943- (Hoboken, New Jersey : John Wiley and Sons, Inc., 2014)
'An accessible, comprehensive guide on magnetic actuators and sensors, this fully updated second edition of Magnetic Actuators and Sensors includes the latest advances, numerous worked calculations, illustrations, and real-life applications. Covering magnetics, actuators, sensors, and systems, with updates of new technologies and techniques, this exemplary learning tool emphasizes computer-aided design techniques, especially magnetic finite element analysis, commonly used by today's engineers. Detailed calculations, numerous illustrations, and discussions of discrepancies make this text an invaluable learning tool for practicing engineers and engineering students'--
'Like the first edition, this book will be for practicing engineers and engineering students involved with the design and application of magnetic actuators and sensors'--
Includes bibliographical references and index.
Keywords: Actuators; Detectors